Obstetric-risk objects: a multi-site, feminist ethnography of private-sector obstetric, maternal and unborn, caring concerns in Cape Town - Daniels, Nicole Miriam (Department of Sociology, 2022)
This thesis contributes to the literature on the management of risk in pregnancy and birth, while examining the impact of technology in shaping risk configurations and articulating knowledge of the unborn. By adopting multiple perspectives on childbirth as a socio-cultural event, I argue that obstetric professional practices are active forces, shaping how pregnancy, childbirth and the unborn become known. Furthermore, a view of both social groups (i.e., obstetricians and pregnant persons) responsible for the management of risks to the unborn, highlights that respectable maternity as a cultural signifier is constructed in collusion with the precepts of medical science. A mixed approach to data collection, utilising a feminist, multisite ethnography helped uncover an interconnected web of relationships and made visible an architecture of risks. Findings are based on observations, indepth, longitudinal interviews, and participant observation with seven obstetricians, a lawyer, an academic, and fourteen pregnant women utilizing six private and one public hospital, obtained over a two-and-a-half-year period in Cape Town, South Africa. I consider various risk objects that configure the caring relationships and re/produce risk sensibilities between obstetricians (as the default caregivers in private sector, middle-class childbirth in South Africa), pregnant, and birthing persons, and the unborn. Obstetric risk objects are here understood to mediate the relationships that emerge between multiple entities and locate the order of importance of risks. Examining the function of high-risk birth as a boundary object, litigation and negligence as intra-acting objects and the unborn as maternal and obstetric work objects, I uncover a hierarchy of structural, organisational, and individual-level risks. I therefore address a gap in the literature on the sociology of risk in childbirth by connecting the top-down structure of power through which institutionalised risk disciplines and constrains behaviour, to the negotiation, and internalisation of risk in everyday life worlds. I thus link macro-structural, maternity systems-risk to meso- institutionalised risk to micro-every day, intimate-risk practices. I use socio-cultural and symbolic theories of risk to account for notions of purity and danger, risk and blame, and vulnerability and power in the configuration of a perfect obstetric professionalism safeguarding access to the sacred unborn. Through finely graded analytical work, woven through with transdisciplinary insights, including from African cosmologies and customary practices, I call for greater collective responsibility to the reproductive capacities that sustain and ensure continuity with all life on earth. Thus, using theory from the south, I propose that ambiguity moves theorisation about reproduction beyond binary positions and further, that it enables conceptions of the unborn to transcend notions of individual, right bearing self-hood. The findings reveal that the preparation, production, and performance of high-risk birth is an already inevitable configuration of private sector childbirth, which explains the exorbitant costs and high rates of interventions that are an obstinate, and historical feature of private sector maternity care in South Africa. High-risk birth is thereby paradoxically and complexly interlinked with the structural preparation of risk within the maternity sector, to its production within a highly at-risk, litigation averse obstetric profession, and to risks ritualised performance in intimate clinical encounters.